2011
DOI: 10.4314/ijbcs.v4i6.64950
|View full text |Cite
|
Sign up to set email alerts
|

Diet supplement effect based on cottonseed meal and <i>Vitellaria paradoxa</i> leaves on Borgou cows performance in rainy season

Abstract: An experiment was carried out to investigate the effect of supplementing lactating cows with cottonseed meal and Vitellaria paradoxa leaves in the rainy season on milk yield and content, cows daily weight gain and profitability. The experimental design was 3 × 3 Latin square with 5 repetitions. Fifteen Borgou cows were offered three diets: grazing on natural pasture, grazing on pasture plus 1.5 kg of cottonseed meal supplement and grazing on natural pasture plus 500 g of Vitellaria paradoxa leaves. Daily milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Foreign breeds such as Holstein Friesian (HF), Brown Swiss and Jersey make up only about 1% of the total cattle population (CSIRO, 2020). Although, Toko et al, (2011) reported that indigenous cows have low milk but are bred and considered a major source of milk, because WF, RB, and SG, are 1st, 2nd, and 3rd highest cattle populations in Nigeria, respectively (Kubkomawa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign breeds such as Holstein Friesian (HF), Brown Swiss and Jersey make up only about 1% of the total cattle population (CSIRO, 2020). Although, Toko et al, (2011) reported that indigenous cows have low milk but are bred and considered a major source of milk, because WF, RB, and SG, are 1st, 2nd, and 3rd highest cattle populations in Nigeria, respectively (Kubkomawa, 2017).…”
Section: Introductionmentioning
confidence: 99%